Developing STEM-Oriented augmented reality activity books integrating candi pari sidoarjo for elementary literacy and numeracy learning - Azis Farkhan; Agung Pramujiono; Via Yustitia (Journal of Advanced Sciences and Mathematics Education, 2026)
Background: Low literacy and numeracy achievement among elementary school students remains a significant challenge in primary education. At SDN Wadungasri, students’ literacy performance showed a decline based on the 2024 educational quality report. Aims: This study aimed to develop an Augmented Reality (AR) Activity Book integrating the local wisdom of Candi Pari to strengthen students’ literacy and numeracy skills through contextual and interactive learning experiences. The novelty of this study lies in combining augmented reality technology with local cultural heritage content to support elementary learning. Method: This study employed a Research and Development approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The product was validated by media, language, and subject-matter experts and tested on elementary school students. Data were collected through validation sheets and student response questionnaires. Results: The findings revealed that the AR Activity Book achieved a very high feasibility level, with an average validation score of 92.1%. Student responses also indicated a highly positive perception, with a satisfaction rate of 91%. Furthermore, the AR-based activity book increased students’ engagement and participation during literacy and numeracy learning activities. Conclusion: In conclusion, the AR Activity Book based on the local wisdom of Candi Pari is feasible and potentially effective in supporting literacy and numeracy learning in elementary schools.